2013
DOI: 10.1371/journal.pone.0057711
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Lactobacilli Isolated from Fermented Slurry (ben-saalga) in Gnotobiotic Rats

Abstract: Most bacterial strains, which have been studied so far for their probiotic functions, are extensively used by manufacturers in developed countries. In our work, we sought to study a mix (called BSL) comprising three strains belonging to Lactobacillus fermentum, L. paraplantarum and L. salivarius, that were isolated from a traditional African pearl millet based fermented slurry. Our objective was to study this BSL cocktail in gnotobiotic rats, to evaluate their survival and their behavior in the digestive tract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 72 publications
0
8
0
Order By: Relevance
“…This is consistent with the stimulation of cell-cycle arrest proteins and the anti-proliferative effect described for lactate in vivo and in vitro ( Rul et al, 2011 ; Matsuki et al, 2013 ). However, we have previously reported that lactate accumulation produced by a mixture of three lactobacilli has no effect on mucus production in gnotobiotic rodents ( Turpin et al, 2013 ). Thus, it is likely that the induction of the mucus pathway requires lactate and additional factors brought by S. thermophilus during its transit through the gut.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…This is consistent with the stimulation of cell-cycle arrest proteins and the anti-proliferative effect described for lactate in vivo and in vitro ( Rul et al, 2011 ; Matsuki et al, 2013 ). However, we have previously reported that lactate accumulation produced by a mixture of three lactobacilli has no effect on mucus production in gnotobiotic rodents ( Turpin et al, 2013 ). Thus, it is likely that the induction of the mucus pathway requires lactate and additional factors brought by S. thermophilus during its transit through the gut.…”
Section: Discussionmentioning
confidence: 94%
“…But, it has been recently shown that a key factor involved in in vitro adhesion of the Lactococcus lactis IBB477 strain did not confer a selective advantage in the intestinal tract of conventional mice ( Radziwill-Bienkowska et al, 2017 ). The ability of lactic-acid bacteria to colonize the gut in animal models harboring a simplified microbiota is not determined by their ability to bind mucus ( Turpin et al, 2013 ). The assumption that high adhesion confers a selective advantage in the gut and provides health benefits is thus not implicit.…”
Section: Discussionmentioning
confidence: 99%
“…When B. thetaiotaomicron is associated with Eubacterium rectale , a representative of the C. coccoides group, both bacteria adapt their own metabolism to the presence of the other [6]. Thus, bacteria in the GIT presumably adapt to the host, and also to other bacteria [40]. In this study, we observed that in mono-associated rats, B. thetaiotaomicron induces goblet cell differentiation leading to an increase in mucin gene expression and goblet cell number, and a parallel decrease in chromogranine produced by enteroendocrine cell.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that aggregation ability is a rare phenotype among lactobacilli (1–2%). Bearing in mind the complexity of the mechanisms and components involved in cell aggregation and adherence, the species specificity, environmental dependence, and contribution to multiple probiotic functional roles [ 11 , 15 , 16 , 17 , 21 , 41 ], we decided to analyze the aggregation-promoting factor specific for Lb . paracasei and its role in collagen binding and pathogen exclusion.…”
Section: Discussionmentioning
confidence: 99%